Analisis Yuridis terhadap Kohabitasi sebagai Tindak Pidana dalam Pasal 412 KUHP Baru - Putri, Dita Melati; Junaidy, Abdul Basith (Media Hukum Indonesia (MHI), 2025)
Indonesia has officially enacted the Draft Criminal Code (RKUHP), which includes various updates to the existing Criminal Code (KUHP). One article that has attracted significant attention is the provision on cohabitation in Article 412. Cohabitation is a complex issue in Indonesia, taking into account social, cultural, moral, and legal values. Cohabitation, or living together without a formal marriage bond, has increasingly become a source of concern in society. The enactment of Article 412 of the Criminal Code reflects a legal response to this phenomenon. The research method used is a normative approach, referring to primary legal materials (the Criminal Code) and secondary sources (previous studies) to provide a deeper understanding of the legal implications related to cohabitation. The research findings indicate a significant increase in the prevalence of cohabitation in major Indonesian cities, which may negatively impact public morality, the spread of sexually transmitted diseases, and the rise of criminal activity. The conclusion of this study is that the enactment of Article 412 provides a clear legal basis for criminalizing cohabitation as an offense aimed at addressing its negative impacts while taking into account the social, cultural, and moral values upheld by Indonesian society.